Pengaruh Penataan Arsip Terhadap Efektifitas Kerja Pegawai Pada Kantor PT. PLN (Persero) UP3 Ambon - Hahury, Jessy Juniu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to find out how the influence of archive management on the work effectiveness of employees of PT. PLN (Persero) UP3 Ambon. The problems faced by PT. PLN (Persero) UP3 Ambon, namely: Not optimal arrangement of archives at the office, where archives are only placed in several containers such as: on cardboard, plastic, or just stacked. As a result, it causes disruption to the archive retrieval process because it is not stored in one good place, thus disrupting the service process for its users and requiring a long time (more than 30 minutes) to search for the required data, whereas in theory The Liang Gie (2007) ) archive discovery standard 1 minute. Simple linear regression analysis according to Riduwan (2010) regression or forecasting is a process of systematically estimating what is most likely to happen in the future. based on past and present information that is owned so that errors can be minimized. used to test the effect of the independent variable (independent) namely the arrangement of files (X) on the dependent variable (the dependent) namely work effectiveness (Y). Arranging archives or managing archives needs to be done properly and maximally, in order to make it easier for employees to carry out their duties so as to increase employee effectiveness. Archival facilities owned by PT. PLN (Persero) UP3 Ambon is not sufficient, only (two) 2 wooden cupboards and several odner folders are available for storing archives. There is no special room for archive storage, so archives are stored in the meeting room or in the employee's office. The lack of facilities as a tool to support the equipment used is also a major factor in the smooth running of the filing process. So far, archive handling has been handled by employees who also hold the position of secretary, causing archive management to be ineffective, because the work being done is not focused on one area. just. Based on the results of partial hypothesis testing, it shows that the Archive Management variable (X) has a positive and significant effect on employee work effectiveness (Y) at PT. PLN (Persero) UP3 Ambon. This is evidenced by the coefficient value of the archive management variable of 4.422 which is greater than t table of 2.048407 and the significant value of the employee work effectiveness variable of 0.00 which is less than 0.05, this means that Ha is accepted. In conclusion, the arrangement of archives affects the work effectiveness of employees at the PT. PLN (Persero) UP3 Ambon.. Â